Association of Estrogen Receptor Genes Polymorphisms With Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis Based on Observational Studies - Zhou, Siyu; Wen, Shu; Sheng, Yongcheng; Yang, Meina; Shen, Xiaoyang; Chen, Yan; Kang, Deying; Xu, Liangzhi (Frontiers in Endocrinology, 2021)
Abstract Purpose: Controversial results existed in amounts of studies investigating the authentic association of estrogen receptor genes (ESR1 and ESR2) polymorphisms with the occurrence and progression of polycystic ovary syndrome (PCOS). The inconsistency might result from different loci, sample sizes and ethnicities. To find the potential correlations between ESR1/ESR2 polymorphisms and PCOS risk, we conducted the first systematic review and meta-analysis to comprehensively summarize current studies in a large combined population. Methods: Eligible studies were retrieved from PubMed, MEDLINE, EMBASE, Cochrane Library, CBM, CNKI, WANFANG and VIP up to February 28, 2021. The quality of studies was assessed using the Newcastle-Ottawa Scale (NOS) scoring system. Odds ratios (ORs) and 95% confidence intervals (95%CIs) were calculated to synthesize data in five genetic models. Subgroup analyses were conducted by ethnicity. Heterogeneity and publication bias were also assessed. The protocol was registered in PROSPERO under the number CRD42021239200. Results: A total of 8 studies involving 1522 PCOS patients and 4198 controls were included. No evidence demonstrated the association of ESR1 rs2234693 (OR=1.07 95%CI 0.98-1.18), ESR1 rs9340799 (OR=0.99 95%CI 0.69-1.43), or ESR2 rs4986938 (OR=1.06 95%CI 0.81-1.38) polymorphisms and PCOS risk in five genetic models. According to stratified subgroup analyses, ethnicity was considered the major source of heterogeneity. No publication bias was found in eligible studies. Conclusion: The present meta-analysis found that no significant associations between the variants of ESR1 rs2234693, ESR1 rs9340799, ESR2 rs4936938 and individual PCOS susceptibility, even if ethnicity was taken into account.